2000
DOI: 10.1111/j.1744-7976.2000.tb00278.x
|View full text |Cite
|
Sign up to set email alerts
|

A Hedonic Analysis of Apple Prices and Product Quality Characteristics in British Columbia

Abstract: The quality and market characteristics of apples have important implications for the merchandising strategy of packers and marketers. A hedonic price function relating apple prices to product and market quality characteristics is estimated for British Columbia over three marketing years (1994–96). The results indicate that grade, cultivar, storage and marketing season are the most significant variables influencing apple prices. The results show that price discounts and premiums for quality characteristics are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 23 publications
1
29
0
1
Order By: Relevance
“…Speciality cultivars such as Royal Gala, Fuji, and Braeburn earned a price premium of $2.25-$2.50 per tray over McIntosh. These price premiums are similar in magnitude for hedonic results reported by Carew (2000) for wholesale apple markets in British Columbia. Speciality cultivars are noted for their juiciness and flavour, and consequently consumers are willing to pay a higher price for them.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Speciality cultivars such as Royal Gala, Fuji, and Braeburn earned a price premium of $2.25-$2.50 per tray over McIntosh. These price premiums are similar in magnitude for hedonic results reported by Carew (2000) for wholesale apple markets in British Columbia. Speciality cultivars are noted for their juiciness and flavour, and consequently consumers are willing to pay a higher price for them.…”
Section: Resultssupporting
confidence: 81%
“…Several studies have employed hedonic price analysis to estimate specific quality characteristics of agricultural (Parker 1993;Oczkowski 1994;Wahl et al 1995;Chen et al 1997) and fish products (McConnell and Strand 2000;Carroll et al 2001). The importance of product quality characteristics (cultivar, grade, size) in determining fresh apple pricing was reported by Carew (2000) for BC, by Kajikawa (1998) for Japan, and by Tronstad et al (1992) for the United States, while Harper and Greene (1993) examined production-related quality attributes (scab, bitter pit, insect damage) for the processed apple market in Pennsylvania.…”
mentioning
confidence: 99%
“…Several previous studies have found the important quality attributes of apple any preliminary analysis [Carew (2000), Huang & Lin (2007), Carew et al (2012), Schollenberg (2012), Gurung, 2013)]. …”
Section: Figure 1 Consumers' Equilibrium Onmentioning
confidence: 99%
“…External appearance factors such as shape, color, and smell provide first impressions about products to consumers which may attract them to try or buy products, while internal attributes such as flavor and texture may influence consumers to purchase those products again. External attributes such as size, grade, cosmetic defects, and storage played a key role in price determination and product demand (Carew, 2000;Kim & House, 2012;Tronstad, Huthoefer, & Monke, 1992). On the other hand, eating-quality factors (internal food attributes) such as crispness, sweetness, acidity, and juiciness considerably influence whether consumers will repeat fruit purchases (McCluskey, Mittelhammer, Marin, & Wright, 2007).…”
Section: Introductionmentioning
confidence: 99%